Influence of age and gender on presentation of symptomatic primary hyperparathyroidism - V N Shah (Journal of Postgraduate Medicine, 2012)
Background: The geographical difference in presentation of primary hyperparathyroidism (PHPT) is known. However, there is sparse literature on the influence of age and gender on presentation of PHPT. Aim: To analyze the effect of age and gender on presentation of symptomatic primary hyperparathyroidism. Setting and Design: This is a retrospective analysis of data from the primary hyperparathyroidism registry of a north Indian tertiary care teaching institute. Materials and Methods: Analysis of 184 histopathologically proven PHPT patients registered between March 1990 and March 2010 from a single centre of north India. PHPT patients were divided into three different age groups i.e. children and adolescents less than 25 years, adults 25-49 years, and ≥ 50 years. Clinical presentations, biochemical parameters and parathyroid weight were compared between different age groups and gender using appropriate statistical methods. Results: Mean age of patients was 38.5±13.8 years with female: male ratio of 7:3. Rickets as presenting manifestations were seen in one child and adolescent each. Prevalence of renal stones (P=0.03) and gall stones (P=0.02) was higher in the adult groups compared to the younger and older. There was no difference in bone pain (P=0.7), fracture (P=0.3), osteitis fibrosa cystica (P=0.2), fatigue (P=0.6) and other symptoms among different age groups. There was no difference in serum calcium, phosphate, parathyroid hormone (PTH) and 25 (OH) D levels among different age groups, however, as expected alkaline phosphatase was higher in adolescents compared to adults (P=0.03). Bone pain and muscle aches (P<0.001), fracture (P=0.04), osteitis fibrosa cystica (P=0.01), and gall stones (P=0.03) were more common among women while renal stones (P=0.05) and pancreatitis (P=0.02) were common in men. Serum calcium and phosphate levels were similar in either sex but parathyroid hormone (iPTH) level was higher among women (P=0.02). Parathyroid adenoma weight was higher in older compared to young but did not reach to a level of statistical significance. Conclusion: Age and gender have substantial influence on presentation of PHPT. Bone pain and rickets were common in children and adolescents while renal stones in adults. Women have more severe disease as musculoskeletal manifestations are common and iPTH levels are also higher compared to men.